Comparison of Outcome between Percutaneous Aspiration, Incision and Drainage In Case of Lactational and Non-Lactational Breast Abscess - Syed Irfan Ali Shah, Sadia Rasheed, Wali Ur Rehman, Kashan Shaikh, Faran Hamid, Zaini Azam (Pakistan Journal of Medical & Health Sciences, 2023)
A breast abscess is a localised collection of purulent material within the breast. Its first-line treatment was incision and drainage under general anaesthesia. But it prolonged the morbidity, whereas aspiration developed as a less invasive solution to the problem. Therefore, this study was conducted to compare the outcome of breast abscess management with both aspiration and incision and drainage techniques. It comprised 60 patients presented at LRH, Peshawar and LUMHS, Jamshoro, (July 2021 to December 2021). The mean age of the presented gyne patients was 34.78+10.55 years. Females with breast abscesses were allocated into two groups carrying 31 and 29 patients in lactational and non-lactational phases, respectively. Results revealed that post-surgical complications including scarring, breast asymmetry, mammary fistula and sepsis were significantly higher (p<0.05) in patients treated with incision and drainage as compared to the aspiration-managed women. Therefore, percutaneous aspiration was found more successful and effective than incision drainage. Keywords: Breast scarring; Mammary fistula; Pus drainage; Surgical complications.